2006
DOI: 10.1080/09540120600568756
|View full text |Cite
|
Sign up to set email alerts
|

Improving well-being through psycho-education among voluntary counseling and testing seekers in Nigeria: A controlled outcome study

Abstract: The present study evaluated the efficacy of an individualized psycho-education (PE) program in reducing psychological distress and risky sexual behavior and enhancing self-disclosure associated with an HIV diagnosis among attendees of a walk-in non-governmental voluntary counseling and testing (VCT) center in Nigeria. Ninety-four consecutive individuals were asked to complete a pre-counseling, baseline questionnaire detailing their sociodemographic characteristics, psychopathology, sexual practices, self-discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…Seven of those reported on an HIV disclosure-related intervention but they did not include disclosure to a sexual partner as their outcome. Rather, outcomes for these studies were disclosure intention [59] disclosure efficacy and anxiety [60], disclosure to children [61, 62] or disclosure to any adults in their social network [63-65]. The remaining three studies were excluded because they did not use an experimental or quasi experimental design [66-68].…”
Section: Resultsmentioning
confidence: 99%
“…Seven of those reported on an HIV disclosure-related intervention but they did not include disclosure to a sexual partner as their outcome. Rather, outcomes for these studies were disclosure intention [59] disclosure efficacy and anxiety [60], disclosure to children [61, 62] or disclosure to any adults in their social network [63-65]. The remaining three studies were excluded because they did not use an experimental or quasi experimental design [66-68].…”
Section: Resultsmentioning
confidence: 99%
“…Case managers at the clinics are also working to deliver emotional support and resolve patients’ problem based on their experiences living with HIV. Intervention studies reported that integration of dialogue and thinking about what needs to be done prior to disclosure, role-playing, and behavioral exercise were more effective than separate interventions in promoting disclosure [53], [54]. There appears to be a role for these types of interventions to enhance disclosure of HIV status and therefore aid in the achievement of optimal adherence and retention in care in Ethiopian patients taking ART as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many international studies investigated different versions of VCT, but limited evidence-based studies were reported for the MSM population [26,49]. Some studies reported theory-based VCT services that effectively reduced the prevalence of sexual risk behaviors [50]. Many of these [17,[31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%